The need of discoursing social theology in Muslim Southeast Asia - Azhar Ibrahim (IAIN Salatiga, 2014)
This paper highlights and evaluates the significance of an emerging social theologicaldiscourse in contemporary Muslim Southeast Asia. It emerged partlyas a response to the traditional Islamic theology inasmuch as the revivalistdakwah activism that became prominent since the 1970s. This emerging discourseis part of the continuity and extension of the reformist voices whichhave evolved since the late 19th century. As a theology, it puts discourse aboutGod as its premium but extend its focus on the social dimension of faith inGod, of the social message of the religion, and the social responsibility of theman and community of faith in God, and to their fellow human beings. Todaythere are several books and articles written which can be classified as belongingto this genre of social theology. In Indonesia this discursive theologycan be found in rational, humanistic, transformative cultural, and the oppressedtheologies. It opens a wider realm of participation and engagement,where theology is no longer the exclusive affairs of experts, but inclusive of thelay intellectuals who are not necessarily from a strictly religious background.It also enables the Muslim public to comprehend critically and to cope creativelywith rapid social change, and its attendant problems. Theology is, afterall, a human enterprise, albeit it’s strong religious commitment. To harnessthe potentiality of the social theology, calls for its recognition. Herein lies the need to start studying and engaging them discerningly, or to advance its criticaldimensions for the benefits of the larger Muslim public.Paper ini menyoroti dan mengevaluasi pentingnya wacana teologi sosial yangmuncul dalam periode kontemporer Muslim Asia Tenggara. Teologi sosialmuncul sebagian sebagai tanggapan terhadap teologi Islam tradisional karenaaktivisme dakwah revivalis yang semakin menonjol sejak tahun 1970-an. Wacanayang muncul di sini merupakan bagian dari kontinuitas dan perluasan suarareformis yang telah berkembang sejak akhir abad ke-19. Sebagai teologi, teologisocial menempatkan wacana utama tentang Tuhan tetapi memperluas fokusnyapada dimensi sosial iman kepada Allah, pesan sosial agama, dan tanggungjawab sosial dari komunitas iman kepada Allah, dan terhadap sesama manusia.Saat ini ada beberapa buku dan artikel yang ditulis yang dapat diklasifikasikansebagai milik genre teologi sosial. Di Indonesia teologi diskursif ini dapatditemukan dalam teologi-teologi rasional, humanistik, budaya transformatif,dan teologi kaum tertindas. Ini membuka sebuah dunia yang lebih luas bagipartisipasi dan keterlibatan, di mana teologi tidak lagi urusan eksklusif paraahli, tetapi termasuk para intelektual awam yang tidak harus berasal dari latarbelakang agama secara ketat. Hal ini juga memungkinkan masyarakat Muslimuntuk memahami secara kritis dan kreatif dalam mengatasi perubahan sosialyang cepat dan problem yang muncul. Di luar itu semua, teologi sosial adalahurusan manusia, dengan komitmen keagamaan yang kuat. Untuk memanfaatkanpotensi dari teologi sosial, diperlukan panggilan untuk pengakuan. Di sinilahletak kebutuhan untuk mulai mengkaji dan melibatkan teologi sosial, ataumengedepankan dimensi kritis dari teologi sosial agar bermanfaat lebih besarmasyarakat Muslim.